Bezkresna przestrzeń na kartce papieru - Muskat-Tabakowska, Elżbieta (Przestrzenie Teorii, 2023)
The paper attempts to introduce Polish readers to a theory presented by the American literary scholar Margaret Freeman in her recent book, The Poem as Icon (2020). In the monograph, Freeman analyzes ways in which the reader experiences reality – both visible and invisible – through poetry. Her fundamental assumption is that the relevant research question is not what literary art is, but how it comes to be what it is. The purpose of the present paper is to show that, although written by a literary scholar, the monograph corresponds to general tendencies that can be seen in contemporary humanities: in cognitive linguistics (in particular, Leonard Talmy’s theory of -ception and George Lakoff’s cognitive theory of metaphor), in the theory of linguistic picture of the world, or in discourse analysis. All these disciplines are based upon the assumption that the essence of the world is continuous change, and they investigate linguistic expressions in the process of becoming, which is relative to factors traditionally considered as non-linguistic. Freeman’s poetic cognition has a wide scope: it embraces cognitive processes of human mind, but also bodily and emotive cognition. Thus poetic cognition is embodied, and in Freemen’s theory a “poem-as-icon” ultimately becomes an illusion of the “here-and-now” direst experience.